2021
DOI: 10.1371/journal.pone.0248464
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics of hospitalized patients during a large waterborne outbreak of Campylobacter jejuni in Norway

Abstract: Very few reports describe all hospitalized patients with campylobacteriosis in the setting of a single waterborne outbreak. This study describes the demographics, comorbidities, clinical features, microbiology, treatment and complications of 67 hospitalized children and adults during a large waterborne outbreak of Campylobacter jejuni in Askoy, Norway in 2019, where more than 2000 people in a community became ill. We investigated factors that contributed to hospitalization and treatment choices. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 27 publications
4
15
0
Order By: Relevance
“…Selection bias may have led to underrepresentation of the elderly and children. The latter is suggested by our previous finding of 17 patients under the age of 16 years in the study that characterized hospitalized patients during the same outbreak [29], whereas the present study found no hospitalized cases under the age of 15 years. Our finding of diarrhea and abdominal pain as the most common, and bloody stools and vomiting as the least common symptoms of acute gastroenteritis in the outbreak setting, is in line with previous literature on Campylobacter infection [8-10, 14, 34, 37].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Selection bias may have led to underrepresentation of the elderly and children. The latter is suggested by our previous finding of 17 patients under the age of 16 years in the study that characterized hospitalized patients during the same outbreak [29], whereas the present study found no hospitalized cases under the age of 15 years. Our finding of diarrhea and abdominal pain as the most common, and bloody stools and vomiting as the least common symptoms of acute gastroenteritis in the outbreak setting, is in line with previous literature on Campylobacter infection [8-10, 14, 34, 37].…”
Section: Discussionsupporting
confidence: 51%
“…The corresponding low proportion of bloody stools observed in the study of hospitalized patients during the Askøy outbreak, can be explained by a possible lowered threshold for referral due to fatal outcome in the initial phase of the outbreak, thus leading to hospitalization of less severe cases [29]. However, virulence factors associated with bloody stools of the particular strain of Campylobacter jejuni cannot be ruled out [29]. Joint pain was more common in our study compared to a Norwegian study of sporadic campylobacteriosis from 1992 (50% vs. 27%) [10], but otherwise seems to be scarcely described in existing literature as a symptom during the acute phase of Campylobacter infection.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from a study conducted in a large urban diarrhea treatment facility in Bangladesh reported frequent presentation of shigellosis with some or severe dehydration in children 13 15 . In the case of Campylobacter infection, we observed no association with inclusion criteria of MSD and our findings were consistent with a study among Canadian children, where dehydration was not reported to be a common presenting feature of Campylobacter -mediated enteritis 16 and a similar finding was observed in a large waterborne outbreak of Campylobacter jejuni in Norway 17 .…”
Section: Discussionsupporting
confidence: 92%
“…In consequence, epithelial barrier destruction and disturbance of the sodium equilibrium lead to a leaky gut syndrome with malabsorption and diarrhea [ 20 ]. In severe and invasive campylobacteriosis cases, inflammatory responses may become overt in extra-intestinal sites and even systemically [ 3 , 6 ]. Furthermore, both, severity of C. jejuni -induced clinical symptoms as well as the risk for development of post-infectious collateral damages have been shown to be directly linked to the sialylation status of the LOS derived from the cell wall of the infecting C. jejuni strain [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In consequence, C. jejuni is transferred to humans from avian livestock via contamination within the food chain. It is known since decades that infected patients present with diarrhea, abdominal pain, vomiting, headache, fever, diarrhea, and bloody stools [6,7]. In otherwise healthy subjects, C. jejuni-induced disease is usually self-limiting and resolves within 10 to 14 days post-infection (p.i.)…”
Section: Introductionmentioning
confidence: 99%